O trabalho com a leitura e a escrita na concepção de três professores da Educação Infantil, em uma escola de Monte Alegre de Goiás - Sousa, Marcilene Oliveira Ramos (Universidade Federal do Tocantins, 2020)
The present work aimed to analyze and understand the reading and writing practices in the conception of three teachers of kindergarten, in a public school in the city of Monte Alegre de Goiás. For the construction of this work, authors who deal with the theme were consulted. such as Antunes (2010), Oliveira (2011), Soares (2004), Baptista (2010), Corsino (2016), among others. This is a qualitative study, based on a field research in which a semi-structured interview with the three teachers was conducted. The study pointed out that the teaching of reading and writing in this stage of education occurs through interactions and play and that even though it is not mandatory that children are literate at the end of this stage, because they are easy to learn, they finish early childhood reading and writing words with simple syllables (formed by consonant and vowel). The teachers also stated that they seek to update themselves with the most recent orientations regarding teaching in the first stage of basic education, especially guided by the assumptions in the Common National Curriculum Base (BNCC), aiming to create meaningful learning possibilities for the children.